Local environment of germanium atoms in Ge3Sb2Te6, Ge2Sb2Te5, GeSb2Te4 and GeSb4Te7 amorphous and crystalline films - Юрий Александрович Петрушин (Physics of Complex Systems, 2023)
The valence state and local environment of germanium atoms in Ge3Sb2Te6, Ge2Sb2Te5, GeSb2Te4 and GeSb4Te7 amorphous and crystalline films were determined by Mossbauer spectroscopy on the 119Sn isotope. In crystalline films, divalent germanium is located in octahedral positions in a rhombohedrally distorted NaCl-type crystal lattice. In amorphous films, tetravalent germanium atoms form a tetrahedral system of chemical bonds. In all the films, the nearest environment of germanium contains mainly tellurium atoms.